2015
DOI: 10.1177/0958928715573485
|View full text |Cite
|
Sign up to set email alerts
|

Low-skill jobs or jobs for low-skilled workers? An analysis of the institutional determinants of the employment rates of low-educated workers in 19 OECD countries, 1997–2010

Abstract: We often hear that the high unemployment rates of low-educated workers in Europe are due to the rigidities of the institutions increasing the labour costs that burden employers. In this article, we challenge this traditional view and offer alternative explanations to the cross-national variation in the employment rate of low-educated workers. Using macro-data and an error correction model, we analyse the determinants of the creation of jobs for low-educated workers in 19 countries between 1997 and 2010. Our fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 46 publications
(78 reference statements)
2
24
0
Order By: Relevance
“…The latter characteristic refers to employment that offers a supply of adequate income, enabling individuals and their families to avoid poverty through labor market participation (e.g. Abrassart, 2015;Marx et al, 2012). This aspect is especially relevant given that multiple actors (the European Commission among others) are promoting a decrease in the gender employment gap as one of the channels to fight poverty.…”
Section: Introductionmentioning
confidence: 99%
“…The latter characteristic refers to employment that offers a supply of adequate income, enabling individuals and their families to avoid poverty through labor market participation (e.g. Abrassart, 2015;Marx et al, 2012). This aspect is especially relevant given that multiple actors (the European Commission among others) are promoting a decrease in the gender employment gap as one of the channels to fight poverty.…”
Section: Introductionmentioning
confidence: 99%
“…While it is difficult to assess effects of job creation across various targets groups using macrolevel data, the macroeconomic evidence largely paints a similar picture as most evaluation studies, where spending on public job creation is found to be detrimental for, for example, employment rates of low-skilled men and women (Abrassart, 2015).…”
Section: Public Job Creationmentioning
confidence: 96%
“…Few authors have discussed this population and those who have chose to focus on the business case for performance improvement among low-skilled employees (Gold & Thorpe, 2008). Women are overrepresented in low-skilled and vulnerable occupations that involve caregiving or provision of service (Abrassart, 2015). Devins and Gold (2014) drew attention to the dearth of HRD literature on the Precariat or the low-skilled employees in low paid jobs who enjoy very little job security and social protection.…”
Section: Focusing On Lives and Experiences Of Different Groups Of Womenmentioning
confidence: 99%